2016
DOI: 10.1111/jcpp.12673
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive therapy as an early treatment for post‐traumatic stress disorder in children and adolescents: a randomized controlled trial addressing preliminary efficacy and mechanisms of action

Abstract: BackgroundFew efficacious early treatments for post‐traumatic stress disorder (PTSD) in children and adolescents exist. Previous trials have intervened within the first month post‐trauma and focused on secondary prevention of later post‐traumatic stress; however, considerable natural recovery may still occur up to 6‐months post‐trauma. No trials have addressed the early treatment of established PTSD (i.e. 2‐ to 6‐months post‐trauma).MethodsTwenty‐nine youth (8–17 years) with PTSD (according to age‐appropriate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 41 publications
1
53
1
2
Order By: Relevance
“…These data support targeting negative appraisals in the psychological prevention and treatment of PTSD. When viewed alongside data from randomised controlled trials that have found a role for such appraisals in mediating treatment response (Jensen, Holt, Mørup Ormhaug, Fjermestad, & Wentzel‐Larsen, ; Meiser‐Stedman, Smith et al., ; Pfeiffer, Sachser, de Haan, Tutus, & Goldbeck, ), the case for making maladaptive appraisals a focus of psychological treatment is strong. A further implication is the need to recognise and address ruminative thinking styles in youth affected by trauma, rather than assuming that the sole cognitive style adopted by youth is avoidance.…”
Section: Discussionmentioning
confidence: 99%
“…These data support targeting negative appraisals in the psychological prevention and treatment of PTSD. When viewed alongside data from randomised controlled trials that have found a role for such appraisals in mediating treatment response (Jensen, Holt, Mørup Ormhaug, Fjermestad, & Wentzel‐Larsen, ; Meiser‐Stedman, Smith et al., ; Pfeiffer, Sachser, de Haan, Tutus, & Goldbeck, ), the case for making maladaptive appraisals a focus of psychological treatment is strong. A further implication is the need to recognise and address ruminative thinking styles in youth affected by trauma, rather than assuming that the sole cognitive style adopted by youth is avoidance.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies were identified among children and adolescents. Among UK children and adolescents with singleincident trauma, Meiser-Stedman et al (2017;high quality) observed changes in rumination and safety-seeking behavior to associate with the effects of individual CT-PTSD on PTSS. When temporal order was established by only looking at changes from start of treatment to midway through it, only changes in safety-seeking remained a significant mediator of pre-post effects on PTSS.…”
Section: Posttraumatic Cognitions and Emotionsmentioning
confidence: 99%
“…Traumatic Memories and Centrality of Traumatic Event A single high-quality study was identified examining changes in traumatic memories as a mechanism of change. Meiser-Stedman et al (2017;high quality) found pre-post changes in self-perceived quality of traumatic memories to be associated with CT-PTSD effects on PTSS among children and adolescents. However, when changes from pretreatment to midway through only were included, in order to establish temporal precedence of changes, no significant mediation was observed.…”
Section: Posttraumatic Cognitions and Emotionsmentioning
confidence: 99%
“…Primary and secondary outcomes were examined first using intention-to-treat (ITT) analysis, followed by treatment completer analyses, as is common practice to provide results of those who complete the trial as well as those who have missing data as a result of dropping out (Luby, Lenze, & Tillman, 2012;Meiser-Stedman et al, 2017;Wood et al, 2009). A sample size of N = 60 was expected to be sufficient to detect large effects, given past studies of CBT interventions for children with ASD (e.g., Reaven et al, 2012), also supported by power analysis (GPower 3.1; with an alpha of .05 and power of 0.8; Cohen, 1988).…”
Section: Data Analysis Planmentioning
confidence: 99%